Análisis de la capacidad física de los trabajadores que operan en las máquinas, servilletera 17, rodumat y empacadoras de la línea Perini 10 del área de conversión en la empresa Productos Familia Sancela del Ecuador - Paillacho Guerra, Evelyn Alejandra (2017)
The study is focused on the analysis of workers’ physical capacity (WPC) of Productos Familia Sancela del Ecuador Industry, from the area of Conversion of the Napkins machines, Rodumat and Balers from the Perini line, in order to know the Physical performance that workers make during the working day; Since the turn of the operators are rotating shifts, influencing their physical state. A human-machine interface diagram was developed to know the activities carried out by the workers and the machine during the eight hours of work, as well as the process diagram of the areas under study was made. Historical data on the body mass index for the years 2015-2016 and 2017 were collected to analyze the data and to classify according to the World Health Organization, in order to know if it is under the optimal standards of weight. The WPC of each operator is evaluated, the maximum caloric expenditure and the energy limit of the workers for a day are calculated; I to order carry out the analysis of WPC, two samples were taken during the day, the first one was taken at the beginning of the turn and the second before the end of the turn, with these data the physical conditioning program was carried out for the workers. In the lifting of loads, the different positions of the workers in the packing and palletizing area were analyzed, and then the data was entered into the E-NIOSH software, getting as result that in the areas mentioned above there is a risk of pain or injury.